Asuhan Keperawatan Pada Tn. H Dengan Congestive heart failure (CHF) - amran, natatsa as syiffa; Asman, Aulia; Gusni, Jufrika; Novariza, Rika (Jurnal Keperawatan Medika, 2025)
WHO revealed that 17.3 million people die each year from heart failure or more than 10% of the world's total deaths (WHO, 2020). According to the Ministry of Health (2021), the prevalence of Congestive Heart Disease in Indonesia reached 900.90 per 100 thousand cases. Based on initial data obtained from an initial survey conducted by researchers on January 20, 2025, data on cases of Congestive Heart Disease in the heart room of Dr. M. Djamil Padang Hospital in 2024 were 195 cases. The purpose of this study is to be able to carry out maintenance on patients with Congestive Heart Disease by including assessment, diagnosis, intervention, implementation, evaluation, and documentation. The case study was conducted in the heart inpatient room of Dr. M. Djamil Padang Hospital from February 17 to 21 with one patient, Mr. H, using the observation and interview methods, physical examination, and documentation. The results of the 5-day case study obtained the diagnosis of decreased cardiac output that had not been resolved with blood pressure of 80/65 mmHg, ineffective breathing patterns that improved sufficiently (RR: 22x/minute), and acute pain improved with the aim of decreasing grimaces, decreasing negative, and decreasing difficulty sleeping. It is expected that Dr. M. Djamil Padang General Hospital can provide optimal health services and good cooperation between health teams and maintain nursing care standards, especially for patients with Congestive Heart Disease..